Greenhouse gas emissions (CO2, CH4 and N2O) in saline-alkaline systems of the Pantanal of Nhecolândia/MS - Melo, Paul Lineker Amaral de (2022)
The Pantanal is recognized as one of the largest wetlands on the planet, one of the main Brazilian biomes and represents an important study environment regarding the emission of Greenhouse Gases (GHG) due to the relatively constant and high temperature of the environment. Given the reality of mitigation and the need to limit global warming to 1.5°C, greenhouse gas emissions in already impacted natural environments have been studied, especially in wetlands. In this work, GHG emissions were evaluated in saline-alkaline systems (lakes and lakes margins - soil) to identify, in two campaigns (2018 and 2019), the behavior and the main processes of formation of CO2, CH4, and N2O gases. For this, four lakes and their margins were selected according to their characteristics identified a priori and classified as black lakes (01SR and 06SR), green lake (04SR), and crystalline lake (07SR). The flow of emissions from the soil of margins was based on different points of saturation by the water of the lakes, with a saturated zone (ZS), an intermediate zone (ZI) and an unsaturated zone (ZI). For this, we also evaluated the carbon stock up to 50 cm depth in the soil. Through principal component analysis (PCA), the chemical variables of the lakes were grouped with the greenhouse gases emitted from the water, while the emissions from the soil in different saturation zones were evaluated by comparing averages. In general, black lakes (01SR and 06SR) were important CO2 emitters, but weak CH4 emitters, both behaviors were more prominent in the second campaign. The green lake (04SR), for the first campaign, was an important CO2 consumer and CH4 emitter, especially due to the presence of methanogenic organisms. However, the behavior of this lake was changed in the second campaign in response to the reduction in the volume of water and the high concentration of nutrients. For this, the consumption of CO2 was impaired and higher emission of CH4 was observed. The Crystalline Lake is the lake that presented the smallest alteration between the campaigns, in both, high emissions of both CO2 and CH4 were observed. For this, the presence of macrophytes is the main vector of gas production. No consistent trend was observed for N2O emission from all lakes. On the margins of the lakes, higher CH4 emission was observed at points of lower oxygenation (saturated zone) with a reduction in their emissions and higher CO2 and N2O emissions when sampling points of higher oxygenation (intermediate and unsaturated zones). Likewise, it was possible to observe that the margins of lakes with a greater presence of grasses were responsible for a greater stock of carbon in the soil